Sistem Pakar Mendiagnosa Penyakit Stroke Transient Ischaemic Attack (TIA) Dengan Menggunakan Metode Dempster Shafer - Maya Lestari; Sulindawaty (Jurnal Sistem Informasi dan Teknologi Jaringan (SISFOTEKJAR), 2021)
Transient ischemic attack (TIA) does not cause permanent brain damage. a transient stroke occurs quickly / briefly within minutes or hours. At this stage, transient ischemic attack (TIA) will mostly attack adults between the ages of 20-45 years. To overcome the Transient ischemic attack (TIA) stroke at the Trianda General Hospital, currently, there are still several obstacles that hinder patients, including because some people do not care about their health, lack of public knowledge about Transient ischemic attack (TIA) stroke, lack of medical personnel. at the Trianda General Hospital, as well as the limited working hours of doctors. The expert system is a doctor substitute system. With the existence of an expert system, it is hoped that it will support patients to directly identify the symptoms of stroke that are felt and know the disease they are suffering from. The existence of this expert system does not mean replacing or eliminating the position of an expert or doctor who is an expert in a particular field, especially in the field of neurological diseases at the Trianda General Hospital, but this expert system will greatly support the role of doctors to diagnose diseases in carrying out further examinations so as to facilitate and speed up the performance of doctors at Trianda General Hospital in diagnosing early mild stroke or Transient ischemic attack (TIA) using a dempster shafer.